2022
DOI: 10.3390/su14148524
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-Resistant Gene Behavior in Constructed Wetlands Treating Sewage: A Critical Review

Abstract: The main objective of this review is to evaluate the performance of constructed wetlands (CWs) used to reduce antibiotic-resistant genes (ARGs) during sewage treatment. To accomplish this objective, statistical and correlation analyses were performed using published data to determine the influence of operational and design parameters on ARG reduction in CWs. The effects of design and operational parameters, such as different CW configurations, seasonality, monoculture and polyculture, support medium, and hydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…VSSF-CW could remove ARGs from wastewater by directly eliminating microorganisms but different ARGs had different removal efficiencies implying the need of a screening of a large number of ARGs for the evaluation of water treatment performances. Overall, these results indicated that the studied wetlands were not able to significantly reduce either the bacterial load of the influent wastewater or the prevalence of most ARGs within the bacterial community (Monsalves et al, 2022).…”
Section: Introductionmentioning
confidence: 84%
“…VSSF-CW could remove ARGs from wastewater by directly eliminating microorganisms but different ARGs had different removal efficiencies implying the need of a screening of a large number of ARGs for the evaluation of water treatment performances. Overall, these results indicated that the studied wetlands were not able to significantly reduce either the bacterial load of the influent wastewater or the prevalence of most ARGs within the bacterial community (Monsalves et al, 2022).…”
Section: Introductionmentioning
confidence: 84%
“…Interestingly, new ARGs may occur in the bacterial population even without antibiotic exposure, as is the case for tetracycline-resistant genes [60]. The resistance of the tetracycline family is a natural phenomenon that gives bacteria adaptive advantages for obtaining resources in the environment compared to other competing species [32]. In addition, tetracycline-resistant genes are highly likely to be transferred to indigenous environmental bacteria and can migrate quickly to the surface of biofilms, especially gene tetW [53].…”
Section: Quantification Of Antimicrobial Resistance Genes By Resistomapmentioning
confidence: 99%
“…ARGs can be removed via biodegradation of the genetic material, antibiosis, adsorption, and filtration [32], of which biodegradation is the primary pathway [33]. Antibiosis is the production of specific antibiotics by fungi or bacteria to inhibit the growth of competing bacteria and thereby decrease ARG abundance [34].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the factorial analysis [18,41], the numeric relation between the factors and the responses can be simulated and shown as following a polynomial regression formula (6). The factorial polynomial regression equations for eight responses are shown as…”
Section: Interactive Effectmentioning
confidence: 99%
“…It also caused potential eutrophication and even the nitrate contamination of groundwater [4]. This issue is of growing concern in remote rural areas and small communities all over the world [5,6].…”
Section: Introductionmentioning
confidence: 99%